Marine Mammals’ NMDA Receptor Structure: Possible Adaptation to High Pressure Environment - Bliznyuk, Alice; Golan, Hava; Grossman, Yoram (Frontiers in Physiology, 2018)
Divers that are exposed to high pressure(HP) above 1.1 MPa suffer from High Pressure Neurological Syndrome(HPNS),which is implicated with central nervous system(CNS) malfunction. Marine mammals performing extended and deep breath-hold dives are exposed to almost 20 MPa without apparent HPNS symptoms. N-methyl-D-aspartate receptor(NMDAR) has repeatedly been implicated as one of the major factors in CNS hyperexcitability as part of HPNS. Electrophysiological studies in rat brain slices at He HP showed a significant increase in the synaptic NMDAR response,followed by postsynaptic excitability changes. Molecular studies of Rattus norvegicus NMDARs have revealed that different subunit combinations of the NMDAR exhibit different,increased or decreased, current responses under He HP conditions. The purpose of the present research was to disclose if the breath-hold deep diving mammals exhibit NMDAR structural adaptation for HP. We used sequence alignment and homology structure modeling in order to compare deep diving marine mammals’ NMDARs to those of terrestrial mammals. We discovered that deep diving mammals have a special tertiary transmembrane-domain(TMD) structure of the GluN2A subunit that differs from that of the terrestrial mammals. In addition,the GluN2A subunit has a group of four conserved a.a. substitutions: V68L(N-terminal domain,NTD) and V440I(agonist-binding domain,ABD) are cetacean specific, E308D(N-terminal domain,NTD) and I816V(TMD) were also singularly found in some terrestrial mammals. Since I816V is localized in M4 α-helix region, which is critical for NMDAR activation and desensitization,we hypothesize that the presence of all 4 substitutions rather than a single one, is the combination that may enable HP tolerance. Furthermore, additional special substitutions that were found in the marine mammals’ NTD may affect the Zn2+ binding site, suggesting less or no voltage-independent inhibition by this ion. Our molecular studies of NMDARs containing the GluN2A subunit showed that HP removal of the Zn2+ voltage-independent inhibition could be the mechanism explaining its current increase at HP. Thus, this mechanism could play a crucial role in the CNS hyperexcitability at HP. Less or no voltage-independent Zn2+ inhibition, different conformations of the TMD,and special mutation in the M4 α-helix region of cetaceans’ NMDAR, may give them the advantage they need in order to perform such deep dives without CNS malfunction.